Respon Peternak Domba Terhadap Aplikasi Teknologi Pakan dan Hormon Reproduksi - Muhammad Matin Muta'Ali; Ulfa Indah Laela Rahmah Rahmah; Lili Adam Yuliandri (Study Program of Animal Husbandry, Faculty of Agricultural, Universitas Majalengka, 2023)
This research was carried out from May to June 2021, and is located in the Majalengka Regency, West Java Province, which is located at the coordinates of 6°48'50.0